PENGARUH DISIPLIN, KOMUNIKASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PADA PT WAHANA LINTAS BATAM - yuvi, yuvi; Rustam, Triana Ananda (SCIENTIA JOURNAL, 2021)
For an organization or agency, human resources are referred to as the main factor as the driving force of the organization Whatever the purpose of an organization, the organization must be formed based on various visions. The purpose of this research is to find out how the effect of Dicipline, Communication, and Work Motivation simultaneously on the job satisfaction of employees of PT Wahana Lintas Batam. This study uses a saturated sampling technique because the population is not large, that is 110 employees. The number of population and sample in saturated sampling is the same. Data analysis was performed using multiple linear regression analysis while the hypothesis test in this study using t test and F test using SPSS Version 25 software program. From the results of hypothesis testing it is known that the variables of dicipline and job satisfaction at PT Wahana Lintas Batam have a significant effect, communication and job satisfaction variables at PT Wahana Lintas Batam have a significant effect, work motivation and job satisfaction variables at PT Wahana Lintas Batam have a significant effect, Dicipline variables, communication, and work motivation together have a significant effect on job satisfaction at PT Wahana Lintas Batam.